2022
DOI: 10.3389/fcimb.2022.892508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Non-Pharmacological Interventions on Dengue Infection: A Systematic Review and Meta-Analysis

Abstract: Non-pharmacological interventions (NPIs) implemented during the coronavirus disease 2019 (COVID-19) pandemic have demonstrated significant positive effects on other communicable diseases. Nevertheless, the response for dengue fever has been mixed. To illustrate the real implications of NPIs on dengue transmission and to determine the effective measures for preventing and controlling dengue, we performed a systematic review and meta-analysis of the available global data to summarize the effects comprehensively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“… 1 The area infested with the mosquito Aedes aegypti is likely to expand due to globalization and climate change, potentially posing even wider health risks. 2 The number of global Dengue infections is estimated to be half a million cases annually. This can lead to hospitalisation and life-threatening symptoms such as Dengue hemorrhagic fever (DHF) and Dengue shock syndrome (DSS).…”
Section: Introductionmentioning
confidence: 99%
“… 1 The area infested with the mosquito Aedes aegypti is likely to expand due to globalization and climate change, potentially posing even wider health risks. 2 The number of global Dengue infections is estimated to be half a million cases annually. This can lead to hospitalisation and life-threatening symptoms such as Dengue hemorrhagic fever (DHF) and Dengue shock syndrome (DSS).…”
Section: Introductionmentioning
confidence: 99%
“…The carriage rate of mosquito-borne viruses in mosquitoes is strongly associated with corresponding mosquito-borne disease outbreaks or epidemics in animals or humans. Numerous studies have demonstrated an overwhelming reduction in the onset of various infectious diseases, which can be attributed to a series of nonpharmaceutical interventions, such as international/internal movement restrictions that discouraged the introduce of travel-associated pathogen, implemented by most countries during the coronavirus disease 2019 (COVID-19) pandemic to suppress its transmission [ 33 , 34 ]. As per official statistics, the incidence of dengue fever in Guangdong, China in 2021 decreased by 99% compared to the previous 5 years, and other mosquito-borne diseases, such as encephalitis B, also witnessed a reduction in the number of cases [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infectious diseases are one of the most important threats to human survival and health and hinder social and economic development. The 2019 novel coronavirus (COVID-19) is the most serious human infectious disease pandemic in the past century [ 1 ]. To curb the transmission of SARS-CoV-2, countries have implemented a diverse array of prevention and control measures, primarily encompassing non-pharmaceutical interventions and vaccination efforts [ 2 ].…”
Section: Introductionmentioning
confidence: 99%